Studies on obesity-related atrial fibrillation in the past 20 years - Bai Du; Jianming Yao; Yingshuo Niu; Chenlu Yuan; Yujie Luan; Xiaohan Zhang; Yuguo Song; Yuanhui Hu; Jiaran Li (Medicine, 2026)
Background: Obesity is a well-established independent risk factor for atrial fibrillation (AF), and its association has been extensively investigated over the past 2 decades. This bibliometric analysis systematically evaluates research hotspots and emerging trends in the field of obesity-related AF. Methods: We extracted data from Web of Science Core Collection and conducted visualization analysis using CiteSpace (Drexel University, Chaomei Chen) and VOSviewer (Leiden University, Centre for Science and Technology Studies) software. Results: Among the 2621 included publications, annual publication counts demonstrated a consistent upward trend. The United States contributed the most studies, with the Mayo Clinic being the most prolific institution and Lip GYH being the most published author. Research in this field spanned multiple disciplines, with circulation as the most influential journal. The most frequent keywords were AF, obesity, and risk factors, along with 20 high-frequency and 25 burst keywords, indicating evolving trends. Conclusion: Through systematic bibliometric analysis, this study highlights key research hotspots and frontiers: cross-disease dimensional analysis, pathophysiological mechanisms, metabolic interventions, the obesity paradox, and AI applications in obesity-related AF. These findings provide a quantitative foundation for future research and offer valuable insights for investigators in this field.